Generalized commutative Jacobsthal quaternions and some matrices - Dorota Bród; Anetta Szynal-Liana (Examples and Counterexamples, 2023)
In this paper, some examples of matrix generators for generalized commutative Jacobsthal quaternions were given. The generating matrices are useful tools for the number sequences satisfying a recurrence relation. They can be used for an algebraic representation and for obtaining some identities.